Bankruptcy : roles of Malaysia department of insolvency (MDI) in financial management / Muhammad Hakim Hasbullah - Hasbullah, Muhammad Hakim (2019)
In Malaysia, the cases of bankruptcy is a normal scenario right now because the cases is increasing year by year. Now days, the trend of bankruptcy faced by young generations has become one of the major concern to the government. This academic project is about, “The roles of Malaysia Department of Insolvency in financial management”. This academic project aims to conduct a detail research about the factors of bankruptcy among people. Besides that, this research intends to determine the function of Malaysia Department of Insolvency (Mdi) in order to achieve their goal regarded the bankruptcy cases. Other than that, this research aim to determine the challenges faced by Malaysia Department of Insolvency (Mdi). The research used a qualitative approach and data was collected from interview. The method in collecting data was directly get form the primary source which is Malaysia Department of Insolvency (Mdi). In addition, Issues that arise in this study are an increase in the number of cases of bankruptcy constantly occurring from time to time. Therefore, this study is conducted to know the roles of Malaysia Department of Insolvency (Mdi) in facing bankruptcy issues in society. In fact, at the end of the study, some suggestions are also mentioned in the role of the Malaysia Department of Insolvency (Mdi). Hence a proposal to raise public awareness about bankruptcy.